2018
DOI: 10.1002/hbm.24388
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in own and other body perception

Abstract: Own body perception, and differentiating and comparing one's body to another person's body, are common cognitive functions that have relevance for self‐identity and social interactions. In several psychiatric conditions, including anorexia nervosa, body dysmorphic disorder, gender dysphoria, and autism spectrum disorder, self and own body perception, as well as aspects of social communication are disturbed. Despite most of these conditions having skewed prevalence sex ratios, little is known about whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 96 publications
(172 reference statements)
2
34
0
1
Order By: Relevance
“…While the difference between gender-potency IAT scores speaks in favor of a higher bias in men, no acrosssample differences in explicit sexist attitudes were observed. Concerning this apparent difference between men's and women's susceptibility to our body swap illusion, recent evidence suggests that sex differences in body perception processes may be relevant to understanding some of our results (35,36). While heterosexual men seem to be more sensitive to self-related information about the opposite sex's bodies, heterosexual women are particularly sensitive to their own bodies (36).…”
Section: Vicarious Reactivity To Virtual Touches On a Virtual Body Thmentioning
confidence: 72%
See 2 more Smart Citations
“…While the difference between gender-potency IAT scores speaks in favor of a higher bias in men, no acrosssample differences in explicit sexist attitudes were observed. Concerning this apparent difference between men's and women's susceptibility to our body swap illusion, recent evidence suggests that sex differences in body perception processes may be relevant to understanding some of our results (35,36). While heterosexual men seem to be more sensitive to self-related information about the opposite sex's bodies, heterosexual women are particularly sensitive to their own bodies (36).…”
Section: Vicarious Reactivity To Virtual Touches On a Virtual Body Thmentioning
confidence: 72%
“…Concerning this apparent difference between men's and women's susceptibility to our body swap illusion, recent evidence suggests that sex differences in body perception processes may be relevant to understanding some of our results (35,36). While heterosexual men seem to be more sensitive to self-related information about the opposite sex's bodies, heterosexual women are particularly sensitive to their own bodies (36). Patterns of brain activation in response to information related to one's own body also differ across sexes: Women seem to engage in complex cognitive-emotional processing more often than men, with activation reported in the amygdala and prefrontal areas (37).…”
Section: Vicarious Reactivity To Virtual Touches On a Virtual Body Thmentioning
confidence: 84%
See 1 more Smart Citation
“…The evaluation of one's body image includes the concerns about body weight and shape, the perception thereof, and the ideal body appearance, linked to a specific mood, selfesteem, and cultural environment [33,34]. Differences in visual body perception have been shown between genders in heterosexual cisgender, with different brain activation linked to their own body and opposite-sex bodies, but no study is available for sexual minorities [35]. The influence of sociocultural aspects linked to body appearance could bring gay men and women to show a higher misperception of their body, but also for this aspect, few studies are available, and bisexual persons are misrepresented in the existing literature [28].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigated brain activation using functional magnetic resonance imaging during a body perception task in healthy males and females. They found that images of their own bodies were more salient for the female participants and concluded that females may be more vulnerable than males to conditions involving own body perception [55]. Youths in Mexico reported higher scores for all the “self-perception regarding weight categories”, than youths in the US.…”
Section: Discussionmentioning
confidence: 99%